Gilvossius chichijimaensis Sakai, 2015 (Crustacea: Decapoda: Axiidea: Callianassidae), a junior subjective synonym of Paratrypaea bouvieri (Nobili, 1904) - Komai, Tomoyuki (Zootaxa, 2017)
Sakai (2015) erected a new callianassid ghost shrimp taxon Gilvossius chichijimaensis diagnosed on the basis of Komai & Tachikawa’s (2008) text and figures of a male specimen originally identified as Paratrypaea bouvieri (Nobili, 1904). A holotype was designated “CBM-ZC 7244, holotype male (cl 7.4 mm), Chichijima Island, Tokyo Prefecture”. This registration number appears to be a mistranscription from Komai & Tachikawa’s (2008) list of specimens which includes “Chichi-jima Island: … CBM-ZC 7422, 2 males (5.2 mm, 7.4 mm), 1 ovigerous female (cl 6.9 mm), Okumura River, rivermouth, tidal flat, 7 August 2002,”. It can be assumed that the second male was selected as the holotype. Although Sakai (2015) did not designate paratypes, he based his comparison of the new species on “the male specimen (CMNH-ZC 2422) identified by Komai & Tachikawa (2008) as Paratrypaea (= Gilvossius) bouvieri”, not the male he selected as holotype. By this he was probably referring to CMNH-ZC 2240.